2021
DOI: 10.3390/plants11010062
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Melanogenic Activity of Calocedrus formosana Wood Essential Oil and Its Chemical Composition Analysis

Abstract: Calocedrus formosana (Cupressaceae) is one of the five precious woods of Taiwan. In this study, we investigated the anti-melanogenic activity of C. formosana wood essential oil (CFEO) and its bioactive components in vitro. Initially, CFEO exhibited strong mushroom tyrosinase activity in the cell-free mushroom tyrosinase assay system with an IC50 value of 2.72 µg/mL. Next, treatment with CFEO significantly as well as dose-dependently reduced a combination of a-melanocyte-stimulating hormone and forskolin (a-MSH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…The active compound that contributed to the superior anti-melanogenesis activities of ( C. unshiu X C. sinensis ) X C. reticulata , C. reticulata , ( C. unshiu X C. sinensis ) X C. reticulata X C. reticulara was found to be terpinene-4-ol because of the presence of a hydroxyl group in the component [ 44 ]. Hsiao et al [ 20 ] evaluated the anti-melanogenesis activity of 11 single compounds including terpinen-4-ol. Among them, the melanogenesis inhibitory activity of thymol was the most superior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The active compound that contributed to the superior anti-melanogenesis activities of ( C. unshiu X C. sinensis ) X C. reticulata , C. reticulata , ( C. unshiu X C. sinensis ) X C. reticulata X C. reticulara was found to be terpinene-4-ol because of the presence of a hydroxyl group in the component [ 44 ]. Hsiao et al [ 20 ] evaluated the anti-melanogenesis activity of 11 single compounds including terpinen-4-ol. Among them, the melanogenesis inhibitory activity of thymol was the most superior.…”
Section: Discussionmentioning
confidence: 99%
“…Various essential oils are widely used for treating physiological dysfunctions of the skin, including hyperpigmentation, acne, skin aging, dry skin, eczema, and dermatitis [ 19 ]. Essential oils from Alpinia zerumbet , Eucalyptus camaldulensis , and Calocedrus formosana are used to alleviate excessive pigmentation conditions such as skin spots [ 20 , 21 , 22 ]. Citrus fruits contain compounds with anti-melanogenesis activities that are potentially suitable for use in whitening cosmetics and hyperpigmentation treatments [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Calocedrus formosana (C. formosana), also known as Taiwan incense cedar, belongs to the Cupressaceae family [172]. The compounds of C. formosana possess the diverse biological effects, such as anti-cancer [173], anti-oxidative [174,175], anti-inflammation [176], and antifungal [177] effects.…”
Section: Calocedrus Formosana Essential Oil (Cf-eo)mentioning
confidence: 99%
“…The compounds of C. formosana possess the diverse biological effects, such as anti-cancer [173], anti-oxidative [174,175], anti-inflammation [176], and antifungal [177] effects. The major components of C. formosana EO (CF-EO) are α-Terpineol, Terpinen-4-o1, and thymol [172]. The treatment with CF-EO inhibits melanogenesis by inhibiting tyrosinase activity and by reducing TRP-1 and TRP-2, co-stimulated with α-MSH and forskolin (FSK), in B16F10 melanoma [172].…”
Section: Calocedrus Formosana Essential Oil (Cf-eo)mentioning
confidence: 99%
“…Several essential oils or their components have been reported to suppress melanin synthesis, such as the essential oils of Melaleuca quinquenervia leaves and stems 16) , Alpinia zerumbet leaves 17) , Eucalyptus camaldulensis flowers 18) , Vitex negundo leaves 19) , and Cinnamomum cassia stem bark 20) . In addition, recent studies have reported that the essential oil extracted from Calocedrus formosana wood reduced melanin synthesis in α-melanocyte-stimulating hormone (α-MSH) and forskolininduced in B16-F10 cells; thymol is the active ingredient responsible for this anti-melanogenic activity 21) . The essential oil of Camellia japonica seeds also exhibits anti-melanogenesis activity in α-MSHtreated B16-F10 cells 22) .…”
Section: Introductionmentioning
confidence: 99%